Grip on the cloud and service grid technologies & some Pain points that clouds and service grids address (International Journal of Engineering and Computer Science, 2013)
Cloud Computing frequently is taken to be a term that simply renames common technologies and techniques that we have come to know in IT. It may be interpreted to mean data center hosting and then subsequently dismissed without catching the improvements to hosting called utility computing that permit near realtime, policy-based control of computing resources. Or it may be interpreted to mean only data center hosting rather than understood to be the significant shift in Internet application architecture that it is. Cloud computing represents a different way to architect and remotely manage computing resources. One has only to establish an account with Microsoft or Amazon or Google to begin building and deploying application systems into a cloud. These systems can be, but certainly are not restricted to being, simplistic. They can be web applications that require only http services. They might require a relational database. They might require web service infrastructure and message queues. There might be need to interoperate with CRM or e-commerce application services, necessitating construction of a custom technology stack to deploy into the cloud if these services are not already provided there. They might require the use of new types of persistent storage that might never have to be replicated because the new storage technologies build in required reliability. They might require the remote hosting and use of custom or 3rd party software systems. And they might require the capability to programmatically increase or decrease computing resources as a function of business intelligence about resource demand using virtualization. While not all of these capabilities exist in today’s clouds, nor are all that do exist fully automated, a good portion of them can be provisioned